1993
DOI: 10.1037/h0079411
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in hospitalized adolescents: Relationship to prior abuse.

Abstract: The effects of admission status, prior abuse, and the frequency and duration of both physical and sexual abuse on measures of suicidality for a sample of 117 hospitalized adolescents were investigated. Having been abused was found to have a significant association with the number of previous suicide attempts and to interact with the variable of admission status in measures of suicide ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 12 publications
2
36
1
Order By: Relevance
“…10,16,17,45 We found that experiencing sexual abuse is a stronger predictor of attempting suicide for male youth than for female youth in this population. Studies in other adolescent populations have shown more emotional and behavioral problems, including suicidality, 17,46 as well as a greater likelihood of perpetration of sexual violence 47 among sexually abused boys than girls.…”
Section: Commentmentioning
confidence: 73%
“…10,16,17,45 We found that experiencing sexual abuse is a stronger predictor of attempting suicide for male youth than for female youth in this population. Studies in other adolescent populations have shown more emotional and behavioral problems, including suicidality, 17,46 as well as a greater likelihood of perpetration of sexual violence 47 among sexually abused boys than girls.…”
Section: Commentmentioning
confidence: 73%
“…One prospective study found no relationship between victimization and adolescent suicide (Brent et al, 1993). Others have found significant differences in child abuse rates between suicidal adolescents and controls (Cavaiola & Schiff, 1988;Shaunesey, Cohen, Plummer, & Berman, 1993). For instance, one study (Brown, Cohen, Johnson, & Smailes, 1999) found that sexual abuse, followed by physical abuse, was associated with the greatest risk of suicidal behavior.…”
Section: Violence Exposurementioning
confidence: 93%
“…Much more devastating outcomes have been reported among sexually abused adolescents such as, a) poor self-esteem (Cavaiola & Schiff, 1989;Bentovim & Boston, 1988;Tong, Oates, & McDowell, 1987) b) suicidal ideation and behavior (Battle, Battle, & Tolley, 1993;Shaunesey, et al, 1993;Garnefski, Diekstra, & de-Heus, 1992). c) substance abuse (Dembo et al, 1988;Rohsenow, Corbett & Devine, 1988;Singer, Petchers & Hussey, 1989); d) involvement in prostitution (Bagley & Young, 1987;Silbert & Pines, 1981); e) sexual confusion and sexualized behaviors (Johnson & Shrier, 1985; f) eating disorders (Hambidge, 1988;Hall et al, 1989;Golfarb, 1987); and, g) delinquency: (Burgess, Hartman & McCormack, 1987;Smith, 1988;Eisenman, 1993).…”
Section: Outcomes Related To Sexual Abusementioning
confidence: 99%